The impact of isolation degree of the alder tussocks on activity and diversity of the epigeic invertebrates - Olejniczka, Izabella; Boniecki, Paweł; Uchmański, Janusz (Studia Ecologiae et Bioethicae, 2011)
Activity and diversity of epigeic invertebrates were studied in 2004, in alder wood (Alnus glutinosa-Carex elata association). There were chosen: fragment of alder wood and 23 alder tussocks that average surface was 0.27m2. There were installed also 16 artificial tussocks: 4 of them were the same size as natural, and the other 12 were smaller, 0,1m2 in size. The average hight of tussockw was 0.4m. Distance between particular tussocks varied from 1 to 2m. Tussocks were placed 3, 5, 7, 9, and 11m from the fragment of the alder wood. The material was collected using pitfall traps. Samples were taken every 7 or 14 days twice in the season: when tussocks were or were not isolated by water. The distance from the alder wood did not influence on activity and diversity of epigeic invertebrates on tussocks. Saprophagous: Isopoda and Collembola and predators: Araneae and Carabidae were the most abundant in the samples.